Association of Statin Use With Disability-Free Survival and Cardiovascular Disease Among Healthy Older Adults - Zhou, Z.; Ofori-Asenso, R.; Curtis, A.J.; Breslin, M.; Wolfe, R.; McNeil, J.J.; Murray, A.M.; Ernst, M.E.; Reid, Christopher; Lockery, J.E.; Woods, R.L.; Tonkin, A.M.; et al. (2020)
© 2020 American College of Cardiology